SISTEM EVALUASI PONDOK PESANTREN MASA ISLAM DATANG - Andini Andini (Al-SAMBASY: Jurnal Kajian Pendidikan, 2024)
This study examines the evaluation system of Islamic boarding schools in facing the challenges of the future of Islam. The main focus is to analyse the need to update the evaluation method to adapt to the times without losing the traditional values of pesantren. The methodology used includes literature study, comparative analysis, and interviews with Islamic education experts. The results showed the need for a more comprehensive evaluation system, covering aspects of religious knowledge, life skills, and readiness to face the digital era. Recommendations include using technology in evaluation, continuous assessment and involving various stakeholders. In conclusion, the proposed evaluation system aims to produce pesantren graduates who are not only experts in religious knowledge but also able to contribute positively in the global society, while still maintaining the identity and values of pesantren.